2021
DOI: 10.1108/ara-06-2021-0104
|View full text |Cite
|
Sign up to set email alerts
|

Value-relevance of reported changes in fair values and measurement-related fair value disclosures: evidence from the Australian real estate industry

Abstract: PurposeThe paper aims to investigate the value-relevance of changes in fair values of investment property reported under International Accounting Standards (IAS) 40 and International Financial Reporting Standards (IFRS) 13.Design/methodology/approachMultivariate regression models are used to regress cumulative market-adjusted stock returns of real estate firms on changes in fair values, along with control variables and corporate governance variables, in order to examine the research question.FindingsUsing hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
0
1
0
Order By: Relevance
“…earnings per share) for UK firms than US firms. Sangchan et al (2021) find that in a sample of Australian real estate companies, fair value changes of investment property under IAS 40 is value relevant to investors. The value relevance is lower for valuation estimates provided by firm directors than those collectively provided by both internal directors and external property valuers.…”
Section: Corporate Governance Structures Of Family-control Real Estat...mentioning
confidence: 86%
See 1 more Smart Citation
“…earnings per share) for UK firms than US firms. Sangchan et al (2021) find that in a sample of Australian real estate companies, fair value changes of investment property under IAS 40 is value relevant to investors. The value relevance is lower for valuation estimates provided by firm directors than those collectively provided by both internal directors and external property valuers.…”
Section: Corporate Governance Structures Of Family-control Real Estat...mentioning
confidence: 86%
“…earnings per share) for UK firms than US firms. Sangchan et al. (2021) find that in a sample of Australian real estate companies, fair value changes of investment property under IAS 40 is value relevant to investors.…”
Section: Relevant Literature and Hypothesis Developmentmentioning
confidence: 86%
“…A key motivation for the support for more fair-value-based income measures comes from the notion that earnings variability under fair-value accounting provides better risk assessment (Ryan 1997). However, previous empirical studies have found mixed results regarding the risk relevance of fair-value income measures (Barth et al 1995;Bratten et al 2016;Hodder et al 2006;Sangchan et al 2022). These studies focus on the incremental volatility of a constructed aggregate fair-value income measure that is derived by adding to GAAP earnings all fair-value gains/losses available from required disclosures.…”
Section: Introductionmentioning
confidence: 98%